Application of Internet-based Cognitive Behavior Therapy Approaches for Female Adolescent with Major Depressive Disorder - Rohmaani, Khadijah Auliaur; Kemala, Cut Nurul (Faculty of Psychology, Universitas Negeri Yogyakarta, 2021)
The purpose of this study was to measure the decrease in depression symptoms experienced by the participant before and after following the intervention by applying the Internet-based Cognitive Behavior Therapy (iCBT) approach. The participant was HN, a 14-year-old female adolescent who refused school due to major depressive disorder. The design of this study was a single-subject design with pre-post measurement. The intervention program was held eight sessions with a pre-session one day before, and a follow-up session was given two weeks after. The instruments used for this research are Beck Depression Inventory-II (BDI-II) to measure depression symptoms and Mood-o-meter, which serves as a mood rating to measure HN's mood fluctuation. This study showed depression symptoms decreased and positive mindset change and behavior towards the social environment at the end of the intervention program.